N-Acetylcysteine and Benfotiamine Protect Autotransplanted Ovarian Tissue From Ischemia-Reperfusion Injury: An Experimental Study - Tuncer, Sevim; Atilgan, Remzi; Pala, Sehmus; Kuloglu, Tuncay; Artas, Gokhan; Aydin, Suleyman (Baskent Univ, 2023)
Objectives: This study aimed to compare the effects of N-acetylcysteine and benfotiamine in protection of ovarian tissue from ischemia caused by slow neovascularization injury due to intraperitoneal ovarian autotransplant in rats. Materials and Methods: Twenty- eight female rats were divided into 4 groups, each containing 7 rats. Group 1 only had the abdomen opened and closed, group 2 was the transplant-only group, group 3 received benfotiamine for 3 weeks starting 1 day before the transplant procedure, and group 4 received N-acetylcysteine for 3 weeks starting 1 day before the transplant procedure. At the end of the experimental period, malondialdehyde levels in ovarian tissues together with the apoptosis and fibrosis, proliferating cell nuclear antigen and vascular endothelial growth factor immunoreactivity, and ovarian reserves were investigated. Results: Apoptosis was significantly increased in group 2 animals. Primordial follicle count was higher in groups 3 and 4 than in group 2. Vascular endothelial growth factor immunoreactivity was decreased in groups 3 and 4 compared with group 2. Proliferating cell nuclear antigen immunoreactivity was reduced in the secondary follicles in all transplant groups. Conclusions: In autologous intraperitoneal ovarian transplant, both benfotiamine and N-acetylcysteine are equal and effective agents in protection of ovarian tissue against ischemic injury.
Keywords: Neovascularization; Ovarian transplantation; Rat; Reactive oxygen species